Awareness regarding Coronavirus pandemic among the population of Sindh, Pakistan: A cross-sectional study - Khalida Shaikh; Areeba Memon; Irfan Ahmed Memon; Zulfiqar Ali Laghari; Abdul Moiz Memon (Sukkur IBA Journal of Computing and Mathematical Sciences, 2020)
Background: The appearance of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) triggered a severe global pandemic and is a major public health issue. As of now, there’s no approved antiviral treatment or vaccine present for this disease. Thus, proper management of such patients and strict practice of precautions by the general public is critical in saving the lives of people affected and stopping the transmission of the disease to those unaffected by it. Methods: This is a cross-sectional descriptive study and was carried out in Sindh, Pakistan. 588 people from different cities of Sindh were asked to fill a questionnaire that tested their attitudes, knowledge and practices related to SARS-CoV-2 pandemic. Results: Television and other social media platforms have led to increased dissemination of knowledge among our population. Their increased understanding has led them to be more compliant with adopting precautionary measures, as frequent handwashing was seen in 89.8% and social distancing in 87.2%. Our results also showed greater prevalence of myths among our population. Conclusion: Increased access to correct knowledge can help to dissipate misconceptions and help spread the accurate knowledge about the role that the public should play in reducing disease transmission.